2017
DOI: 10.33549/physiolres.933522
|View full text |Cite
|
Sign up to set email alerts
|

An Alternatively Activated Macrophage Marker CD163 in Severely Obese Patients: the Influence of Very Low-Calorie Diet and Bariatric Surgery

Abstract: CD163 is a marker of macrophages with anti-inflammatory properties and its soluble form (sCD163) is considered a prognostic predictor of several diseases including type 2 diabetes mellitus (T2DM). We explored sCD163 levels at baseline and after very low-calorie diet (VLCD) or bariatric surgery in 32 patients with obesity (20 undergoing VLCD and 12 bariatric surgery), 32 obese patients with T2DM (22 undergoing VLCD and 10 bariatric surgery), and 19 control subjects. We also assessed the changes of CD163 positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…CD163, with a molecular weight of 130 kDa, is the high-affinity scavenger receptor for the hemoglobin–haptoglobin complex found in 1987 17. CD163 is famous as a marker of activated macrophage (M2 macrophage) in many immune disorders and inflammation-related diseases, such as obesity, chronic graft-vs-host disease, pulmonary tuberculosis and cardiovascular diseases 1821. Recently, CD163 was identified as an important indicator for tumor-associated macrophages that were demonstrated to be strongly correlated with tumor aggressiveness in many types of cancers including gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CD163, with a molecular weight of 130 kDa, is the high-affinity scavenger receptor for the hemoglobin–haptoglobin complex found in 1987 17. CD163 is famous as a marker of activated macrophage (M2 macrophage) in many immune disorders and inflammation-related diseases, such as obesity, chronic graft-vs-host disease, pulmonary tuberculosis and cardiovascular diseases 1821. Recently, CD163 was identified as an important indicator for tumor-associated macrophages that were demonstrated to be strongly correlated with tumor aggressiveness in many types of cancers including gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Positively correlated with central adiposity and insulin resistance[50, 51]CD 163Marker of macrophages with anti-inflammatory properties. Increased basal CD163 levels are related to obesity and its metabolic complications[60, 61]CD 206Marker of M2-like macrophages in adipose tissues. Inhibits growth and differentiation of adipocyte progenitors, thus controlling adiposity and systemic insulin sensitivity[62]ArginaseMarker of M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary endpoints are (1) the differences in levels of other proinflammmatory and anti-inflammatory mediators in blood, subcutaneous tissue, and visceral adipose tissue, namely (a) inflammatory mediators associated with neutrophils: metalloprotease (MMP)-2 [3638], MMP-9 [36], CXCR2 [39], IL-12 [40], CCL3 (macrophage inflammatory protein (MIP)-1α) [4144], CCL2 (MCP1) [44], IL-1β [45], TNF-α [46], NRF2 [47, 48], (b) mediators associated with macrophages: proinflammatory (IL-1β, CD40 [49], CD80 [50]), M1 phenotype markers (TNF-α, IL-6 [5153], iNOS [5456]), anti-inflammatory (IL-1 receptor antagonist (IL-1RA) [5759], NrF2), M2 phenotype markers (CD163 [60, 61], CD206 [62], arginase [63, 64], IL-10 [65], transforming growth factor (TGF)-β1 [6668]), and (c) mediators associated with cell death pathways (BCL2-associated X (Bax), bcl2 [69, 70], caspases 3 and 9 [7173]); (2) intraoperative complications: (a) hypoxemia (PaO 2 /FiO 2 ratio < 300), (b) hypotension (systolic blood pressure < 90 mmHg), (c) bradycardia (heart rate < 50 bpm), (d) unexpected need for intensive care unit (ICU) admission or readmission, (e) length of hospital stay, (f) number of days at home in the first month after surgery, and (g) postoperative complications: pulmonary infection (defined as new or progressive radiographic infiltrate and at least two of the following criteria - antibiotic treatment, axillary temperature > 38 °C, leukopenia (WBC < 4000 cells/mm 3 ) or leukocytosis (WBC > 12,000 cells/mm 3 ), and/or purulent secretions); sepsis (defined as suspicion or certainty of infection and an acute increase ≥ 2 points in the Sequential Organ Failure Assessment Score (SOFA) in response to an infection, representing organ dysfunction); septic shock (defined as sepsis plus need for vasopressor to maintain mean blood pressure > 65 mmHg plus lactate > 2 mmol/L [18 mg/dL] after adequate volume resuscitation [7476]); extrapulmonary infection (of the operative wound or any other infection); coma (Glasgow Coma Scale < 8 in the absence of therapeutic sedation); acute myocardial infarction (according to the universal definition thereof [77]); acute kidney failure (according to the risk, injury, failure, loss, end-stage renal failure (RIFLE) criteria classification system [78]); DIC (according to the International System for the Evaluation of Thrombosis and Hemostasis for DIC [79]); GIF (defined according to the GIF score [80]); acute liver failure (defined as a ratio of total bilirubin on the 5th postoperative day to the 1st postoperative day > 1.7 plus a ratio of international normalized ratio (INR...…”
Section: Methodsmentioning
confidence: 99%
“…Although diet and nutrients are known to modulate the activation status of CD163+ macrophages [4,9], questions remain as to the type of diet and nutrients that affect the shedding of the surface CD163 receptor from macrophages. Energy restriction-mediated weight reduction (e.g., bariatric surgery or a hypocaloric diet) decreased sCD163 levels, and changes in sCD163 levels were associated with improvements in metabolic dysfunction [1,10,11,12]. Currently, the direction of causal relationships among weight loss, sCD163, and metabolic improvement remains undefined [7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the direction of causal relationships among weight loss, sCD163, and metabolic improvement remains undefined [7]. sCD163 levels decreased in response to bariatric surgery [10], a hypocaloric diet [1,10], and lifestyle interventions (a combination of physical activities and caloric restrictions) [12] but not exercise [1] or physical activity [12]. Fjeldborg et al showed that moderate intensity exercise without dietary restriction did not effect on sCD163 levels despite of losing 3.5% of their initial body weight [1].…”
Section: Introductionmentioning
confidence: 99%